59PPattern of care in high-grade gliomas after recurrence. (24th November 2019) - Menon, N; Simha, V; Abhyankar, A; Kalra, D; Krishnatry, R; Gupta, T; Jalali, R; Patil, V M
Abstract: Background: Relapse or progression in glioblastoma is common. Multiple options ranging from local treatment like re-surgery, re-radiation to systemic therapies like bevacizumab, CCNU, etc. are available. Patients with longer progression-free interval (> 2 years), smaller volume of disease and disease in non-eloquent areas are preferably selected for local therapies and while the others receive systemic therapy. There is limited data available on the pattern of care in relapsed gliomas hence we conducted an audit to address this deficiency. Methods: A prospective database of all glioma patients has been maintained from June 2015 onwards at neuro-oncology DMG (Disease Management Group) at the Tata Memorial Hospital. We analysed the data of patients with relapsed gliomas treated from June 2015 to December 2017. Results: The database had 854 patients of which 749 (87.7%) had disease progression. The treatment received by these 749 patients were best supportive care in 519 (69.3%), local therapy with or without systemic therapy in 85 (11.3%) and systemic therapy in 145 (19.4%) patients. Local therapy consisted of re-surgery (with or without re-radiation) in 63 patients and re-radiation (with or without systemic therapy) in 23 patients. The systemic therapies received were salvage temozolomide in 79 patients, bevacizumab (with or without an additional agent) in 41 patients and CCNU in 25 patients. The factors associated with administration of therapy at relapse were age (p = 0.009) and family income (0.041). The other factors tested were gender (p = 0.311) and performance status at relapse (p = 0.637). Conclusions: This data highlights that a large number of patients with recurrent gliomas do not receive any treatment (69%), which is similar to the pattern of care reported from Australia. The pessimism associated with treatment of relapsed glioma is due to dismal prognosis at relapse with the current therapy available. Legal entity responsible for the study: Tata Memorial Hospital. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.